Fluctuations in Moyamoya Vasculopathy Associated with Basedow Disease Depending on Thyroid Hormone Status - Masaoki Hidaka (Case Reports in Neurology, 2020)
A 31-year-old woman presented with sudden onset of weakness in her left upper limb. Magnetic resonance imaging revealed acute cerebral infarctions in the right frontal and parietal lobes. Magnetic resonance angiography showed stenosis in the proximal portions of the bilateral middle cerebral arteries and terminal portions of the bilateral internal carotid arteries. The patient also complained of thyrotoxic symptoms, such as tachycardia, goiter, and fine finger tremor. She was diagnosed with acute ischemic stroke due to moyamoya vasculopathy (MMV) associated with Basedow disease. The patient’s thyroid hormone status normalized and intracranial artery stenosis gradually improved. However, after 6 months, she developed transient left hemiparesis during the 7th week of gestation. Her thyroid function deteriorated, and MMV progressed. Then, MMV improved again with the normalization of her thyroid function. This case shows that MMV associated with Basedow disease could worsen or improve depending on the thyroid hormone status.